Effects of Probiotics on the Expression and Localization of Avian β-defensins in the Proventriculus of Broiler Chicks - Elsayed S. I. Mohammed; Yasumi Igarashi; Naoki Isobe; Yukinori Yoshimura (The Journal of Poultry Science, 2015)
The aim of this study was to determine the effects of probiotics-feeding on the gene expression and protein localization of avian β-defensins (AvBDs) in the proventriculus of broiler chicks. Male broiler chicks were arranged in 3 groups: control group, probiotics group I and probiotics group II, which were fed with starter rations containing 0%, 0.2% or 0.4% probiotics, respectively, from day 0 (D0; at one day old) to D14. Proventriculi in all groups were collected at D0, D7 and D14 for analysis of AvBDs expression and AvBD12 protein localization. The expression of AvBDs genes was examined by reverse transcription-PCR and changes in the expression upon probiotics-feeding were examined by real-time PCR. The AvBD12 localization was examined by immunohistochemistry, and density of immunoreaction products was examined by image analysis under a microscope. Out of 14 AvBDs genes, seven AvBDs were detected in the proventriculus of chicks, namely, AvBD1, 2, 4, 6, 7, 10 and 12. The expression of the 7 detected genes did not show any significant differences between control and probiotics groups at D7 and D14. The immunoreactive (ir) -AvBD12 was localized in surface epithelium and cells in the connective tissues of proventricular glands. The ir-AvBD12 density in surface epithelium was significantly higher at D7 than at D0 or D14 in control group. At D7 and D14, the ir-AvBD12 density was significantly lower in probiotics groups than in control group. The ir-AvBD12 cells in proventricular gland increased in number with age; however, there were no significant differences between control and probiotics groups at D7 and D14. These results suggest that, although probiotics-feeding does not affect the gene expression of AvBDs, it may induce AvBD12 secretion from the surface epithelium of the proventriculus in broiler chicks.